Effect of time of planting on growth, fruiting behaviour and sex relations of papaya (Carica papaya) - SINGH, A K; SINGH, GORAKH (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994-96 at Lucknow on the effect of different planting times (August, September, October, November, December, January and February) on growth and fruiting behaviour and sex expression (male, female and hermaphrodite) of’ Pusa Delicious’ papaya (Carica papaya L.) was investigated. Plant height, stem girth and canopy spread (north-southleast-west) during successive stages of plant growth were significantly if (P < 0.05) influenced by different planting times. After 16-month age, significant (P < 0.05) increase in the plant height (252.71 cm) and stem girth (41.66 cm) was observed in September planting except in December where it was at par with September planting. Maximum canopy spread was attained in north -south I east -west direction (221.50/235.50 cm) in September planting. These findings also hold good for the October planting. Overall, the rapid increase in plant height, stem girth and canopy development was obtained between 4-and 10-month age and beyond this the rate of growth was found to be low. October and September plantings produced minimum male plants ( 11.12 and 15.0% respectively) and maximum female and hermaphrodite plants (61.10 -27.28% and 65.0 - 20.05% respectively). Of the different month of planting , the highest yield (61.87 kg / plant) was obtained in September planted papaya. This was closely followed by October planting. However, November planting was found comparatively safer from papaya ring spot virus disease. Warmer and intermediate temperature with wider diurnal tmCtuation gave congenial conditions of plant growth and production of papaya.